COMPOSITION OF THE ESSENTIAL OIL OF MARRUBIUM ANISODON C. KOCH - Kirimer, N.; Kürkçüolu, M.; Akgul, G.; Baser, K. Hüsnü C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The genus Marrubium (Labiatae) is represented by 23 taxa, 13 of which are endemic to Turky(1). Aerial parts of Marrubium anisodon were subjected to hydrodistillation for 3h using a Clevenger-type apparatus. Essential oil of the plant material from Turkey was analysed by GC and GC/MS. Thirty-nine components were characterized in total, representing 87.9 % of the oil. (Z)-farnesene (20.2 %), nonacosane (18.5%) and caryophyllene (13.3 %) were main constituents. References: 1. Cullen, J., 1982, Salvia, Flora of Turkey and East Aegean Islands; Univ. Press: Edinburgh, P.H. Davis (Ed.), Vol.7, 165-178.